Nonlinear dynamic analysis of a two-phase natural circulation loop with multiple nuclear-coupled boiling channels - Lee, Jin Der; Pan, Chin; Chen, Shaw Wen (Annals of nuclear energy, 2015)
•Type-I and type-II instabilities exist in different natural circulation systems.•The thermal-hydraulic system presents in-phase mode over the type-I boundary.•Out-of-phase mode generally distributes along with the type-II boundary.•In-phase will dominate over out-of-phase as increasing the neutronic feedback.•Complex nonlinear phenomena appear in the nuclear boiling natural circulation loop. This study integrates the models developed previously by the authors to explore the stabilities, nonlinear dynamics and oscillation modes of a two-phase natural circulation loop with multiple nuclear-coupled boiling channels. The results indicate that both the pure thermal-hydraulic and nuclear-coupled boiling systems indeed have two instability regions, i.e. type-I and type-II instabilities, respectively. The pure thermal-hydraulic system tends to present in-phase mode of oscillations at the type-I boundary states and, in general, out-of-phase oscillations along with the type-II stability boundary. The oscillation modes may be affected by the configuration of parallel channels. By introducing the void-reactivity feedback together with neutron interaction, the coupling thermal-hydraulic and nuclear effects would induce complex influences on the system stability as well as the nonlinear oscillation modes. The in-phase mode, instead of out-of-phase mode, majorly dominates over the type-II boundary as the neutronic feedback is increased through void-reactivity coefficient. The complex nonlinear phenomena, such as complex periodic and chaotic oscillations, may appear in this multi-channel nuclear-coupled boiling natural circulation loop subject to a strong void-reactivity feedback (3Cα) coupled with a weak subcore-to-subcore neutron interaction (ɛij=7.0).